Trends in global literary studies: Mapping using Open Access (OA) journals database - Ahmadi, Anas (citeus, 2021)
Currently, the study of journal mapping is in great demand by researchers from various disciplines, one of which is the literary discipline. Mapping literary research allows for the presentation of statistics on literary research that is currently trending or less desirable. This study aims to map trends in literature studies globally from 2015 to 2019. The method used in this research is descriptive qualitative with interpretive-narrative techniques. The data used in this study were international journal literature category with Open Access (OA) criteria obtained from the ScimagoJR database. The data used are 10 literary journals in the Open Access category. The data were collected using documentation technique. Data analysis techniques in this study include identification, classification, reduction, analysis, presentation, mapping, and conclusions. The results showed that the trend of literary research in the Open Access database changes every year. In the 2015-2019 period, trends in literary studies that were found include philosophy, translation, feminism, anthropology, and interdisciplinary studies. The conclusion shows that the highest ranking of literature studies in the Open Access database is translation. Saat ini studi mengenai pemetaan jurnal sangat diminati oleh peneliti dari berbagai disiplin, salah satunya adalah disiplin sastra. Melalui pemetaan penelitian sastra dapat diketahui penelitian sastra yang saat ini tren ataupun penelitian sastra yang kurang diminati. Penelitian ini bertujuan untuk memetakan tren studi sastra secara global mulai tahun 2015 hingga 2019. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan teknik interpretatif-naratif. Data yang digunakan dalam penelitian ini adalah jurnal internasional kategori sastra dengan kriteria Open Access (OA) yang diperoleh dari database ScimagoJR. Data yang digunakan adalah 10 jurnal sastra kategori Open Access. Teknik pengumpulan data dilakukan secara dokumentatif. Teknik analisis data dalam penelitian ini meliputi identifikasi, klasifikasi, reduksi, analisis, penyajian, pemetaan, dan simpulan. Hasil penelitian menunjukkan bahwa tren penelitian sastra dalam database Open Access mengalami perubahan setiap tahun. Dalam kurun waktu tahun 2015-2019 ditemukan tren studi sastra, yaitu filsafat, penerjemahan, feminisme, antropologi, dan interdisipliner. Kesimpulannya menunjukkan bahwa peringkat tertinggi studi sastra dalam basis data Open Access adalah penerjemahan.